Risk Perception and COVID-19 Transmission Experiences in Indonesia 2022 - Sapto Budi Nugroho; Mila Tejamaya (Universitas Airlangga, 2023)
Introduction: The COVID-19 pandemic in Indonesia has not officially ended, and due to the apparent underestimation of protective behavior, it is imperative to continuously promote public awareness and implement health protocols to control its spread. Therefore, this study aims to analyze the community's risk perception and experiences of COVID-19 transmission in Indonesia. Method: This study was conducted in 2022 using an online survey. The questionnaire was developed based on a standard questionnaire (ECOM, 2015) on the risk perception of an infectious disease outbreak. It was then distributed through various social media platforms, including WhatsApp, Facebook, and Instagram. Result: According to all ten risk perception distribution data, the majority of respondents considered COVID-19 a threat. This showed that most respondents had intense COVID-19 transmission directly or indirectly. This study also revealed that there were more female respondents than men. Conclusion: Individuals who had contracted COVID-19 might have different perceptions compared to those who had not been infected. Furthermore, experiences such as the COVID-19 transmission involving relatives and friends might also shape an individual's risk perception, particularly in implementing protective behavior, in this case, health protocol. Control measures based on gender should also be considered to ensure the effectiveness of the COVID-19 risk management.